Psoriasis as a problem in surgical practice - Mikiel, Dominik; Kapała, Wojciech; Neneman, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
This article focuses on the problem of psoriasis as a dermatological disease that may be a complication during surgical procedures. Defined problems, for patients with psoriasis if they undergo surgery, are often connected with the drugs they use for treatment, which can influence the immune system and wound healing. Some examples of surgical procedures, that are documented to cause a substantial improvement of the skin condition in patients with psoriasis, are also presented in this article. Moreover, the fact that each traumatic procedure on patient with psoriasis may aggravate or even induce skin lesions is also mentioned.